Perceived barriers to the process of COVID-19 control among frontline healthcare workers in South Korea: a qualitative study - Heeyoung Lee; Myoungsoon You; Bee-Ah Kang; Sijoung Kwon (BMJ Open)
Objective This study aimed to explore barriers to disease control perceived by frontline healthcare workers (HCWs) working in community settings during the COVID-19 pandemic in South Korea.Design A qualitative study was conducted using semistructured focus group interviews. All interviews were conducted in Korean on Zoom between October and November 2020, audio-recorded and transcribed for reflexive thematic analysis.Setting All participants were working in Gyeonggi-do, the most populous province in South Korea. The province had the second-highest COVID-19 infection rates at the time of the interview.Participants Participants serving as HCWs in Gyeonggi Province were eligible to participate in the study. A total of 20 HCWs comprised of public health doctors and professional epidemiologists agreed to participate in the study.Results Four themes were generated. Each theme described how these barriers affected a disease control process: (1) ‘uncooperative public and unprepared community health centre’ delayed the investigation of newly diagnosed COVID-19 cases; (2) ‘uncoordinated disease control system’ impeded the collection and analysis of digital data; (3) ‘the gap between responsibilities and capabilities’ hindered the classification of close and casual contacts; and (4) ‘conflicts with persons who have different interests and priorities’ hampered epidemiological decision-making.Conclusions Our study found that frontline HCWs experienced various challenges disrupting their work performance to control COVID-19. We provide several recommendations, such as providing HCWs with systematic interview skill training, strengthening patient information security systems, providing sufficient resources, securing a regular workforce, collecting the field experiences of HCWs, implementing task-shifting, and having regular stakeholder meetings. These strategies may promote work capacity among the frontline HCWs and subsequently strengthen emergency preparedness.